Estudo da composição química do óleo essencial de Lippia microphylla Cham em três anos diferentes e atividade antioxidante - Silva, Mauro Marcos da (2014)
The state of Roraima is divided into three major ecological systems: forests, meadow-campinarana and savannas, and are located in the extreme north of the Brazilian Amazon. Despite the wide variety of plants there is little information on herbs of the region. The Lippia microphylla Cham., belongs to the family Verbenaceae and the genus Lippia, popularly known as salva-do-campo being found in the Roraima savannas. This plant is easily found along the margins of the BR 174, the route Boa Vista, Brazil, to the Santa Elena de Uairén, Venezuela. The aim of this study was to evaluate the chemical composition of essential oil of Lippia microphylla Cham. Collected at different times and schedules and analyze their antioxidant activity. The samples were collected in Boa Vista, Roraima, at three different times ( 8, 12 and 18 hours ) in May 2009, 2010 and 2011, for realization of antioxidant activity the samples were collected in the month of March 2011. The leaves were extracted by hydrodistillation with the assistance of a Clevenger apparatus and the oils analyzed by Gas chromatography coupled with mass spectrometry, GC-MS. To determine the antioxidant activity of the essential oil the method of sequestering ability of the free radical DPPH was used. The highest yields of oils were recorded in May 2011, which recorded highest rainfall month, but it did not rain on the day of collection. The analysis of the constitution of the oils revealed that thymol, carvacrol, E-caryophyllene, nerolidol and caryophyllene oxide were the main constituents of which the majority carvacrol was in almost all analyzes. The best antioxidant capacity oil was extracted from material collected at noon containing higher concentration of thymol ( 9.22% ) and carvacrol ( 19.80% ). We observed that the oils collected in different years showed significant differences in their chemical composition and yield. The rain on the day of collection was more important than the volume of rainfall in the month. The antioxidant activity of these oils can be attributed mainly to the presence of two phenolic isomers.